Disclosure of expectation gaps: Determinants and influence on the level of public trust in privilege funds - Mufidta, Fenny; Urumsah, Dekar (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
The public expectation gap is an issue that is often discussed in the management of privilege funds. The public expectation that privilege funds can be used to finance various sectors is one of the gaps in expectations. Trust is key in synergizing or connecting the state, government and society. However, the discrepancy between public expectations and the existing conditions for managing the privilege fund is one of the causes of the expectation gap. This prompted this study to analyze the factors of the expectation gap that affect the level of public trust in the management of privilege funds. This research uses a quantitative approach with descriptive content analysis. The object of research is people who live in the Special Region of Yogyakarta. Data sources came from respondents through offline and online questionnaires. The analytical tool relies on SmartPLS 4.0, this refers to the number of samples used is not large but the model built is complex. The findings show that the public expectation gap affects the decline in the level of public trust. This research is expected to help identify problems that arise due to a mismatch between expectations and reality. So that it can restore public confidence that tends to feel disappointed and grow suspicion in the implementation of privilege fund activities. With the improvement or adjustment of policies that are more in line with public expectations, the public will feel more valued and recognized. This can increase public participation in planning, monitoring and program implementation. So that it will not lead to a crisis of legitimacy for the concept of privilege itself.